Developing esltpackhub for tpack development of esl pre-service teachers: Preliminary usability evaluation insights - Noraini Said; Nur Suhaidah Sukor; Elaine Ting Pick Dew (International Journal Of Modern Education (IJMOE), 2024)
This article presents a usability evaluation of a portal on a Canva platform, known as ESL TPACK HUB which was developed to support the Technological Pedagogical Content Knowledge (TPACK) development of ESL pre-service teachers. The evaluation involved getting insights from two groups of subjects: three content and instructional design experts, and five ESL pre-service teachers in Sabah. Semi-structured interviews and feedback forms were adopted as the qualitative data sources to answer the research question. Four main usability criteria were focused on: the portal's visual design, functionality, content, and overall usefulness. The results indicate that the subjects perceive the portal as user-friendly, as they were able to access all five main components: video tutorials on ESL websites, digital applications and innovations for language lessons, lesson plans and a curated list of ESL websites. Additionally, participants found the demonstration videos for apps and websites particularly helpful, including the videos integrating multiple ICT tools in a language lesson. The content of the portal was deemed engaging, comprehensible, and highly pertinent to the TPACK development of preservice teachers. The participants also agreed that the portal's functions effectively meet users' needs. However, minor technical issues were identified, notably in the loading speed of the videos, which require attention. These findings are critical in informing the iterative design and development phases of the instructional design model for this portal. Addressing the identified issues is essential to ensure the successful implementation of TPACKsupporting applications in teacher education programs.